2016
DOI: 10.4103/0019-5413.181779
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of pedicle screw fixation in dorsolumbar spine by freehand versus image-assisted technique

Abstract: Background:New and expensive technology such as three-dimensional computer assisted surgery is being used for pedicle screw fixation in dorsolumbar spine. Their availability, expenses and amount of radiation exposure are issues in a developing country. On the contrary, freehand technique of pedicle screw placement utilizes anatomic landmarks and tactile palpation without fluoroscopy or navigation to place pedicle screws. The purpose of this study was to analyze and compare the accuracy of freehand and image-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A cadaveric study done by Agarwal et al found the sensitivity and specificity of postoperative CT scans to pick up pedicle screw breach was 91.52% and 95.02% respectively [ 35 ]. However, not all patients with pedicle breaches present with neurological deficits [ 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cadaveric study done by Agarwal et al found the sensitivity and specificity of postoperative CT scans to pick up pedicle screw breach was 91.52% and 95.02% respectively [ 35 ]. However, not all patients with pedicle breaches present with neurological deficits [ 36 39 ].…”
Section: Discussionmentioning
confidence: 99%